2022
DOI: 10.1111/faf.12672
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences in influencing and shaping small‐scale fisheries governance

Abstract: This paper synthesizes current empirical evidence on how women experience, shape and influence small‐scale fisheries (SSF) governance. Our synthesis addresses an important gap in the literature, and helps highlight the opportunities to improve women's participation in governance and advance gender equality. We identified, characterized and synthesized 54 empirical cases at the intersection of gender and SSF governance, which comprise the relevant body of literature. Our review confirms the need to embed gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 104 publications
(190 reference statements)
2
15
0
Order By: Relevance
“…Specifically, we focus on how women in the SSF sector have responded to the disruptions caused by COVID-19 and assess the resilience-potential of these responses based on how these responses interact with their pre-existing SSF vulnerabilities. This line of inquiry has critical importance, given the high degree of vulnerability that existing research within SSF has recognised among women within this sector (see, for instance, Thorpe et al, 2014;Harper et al, 2017;Galappaththi et al, 2022;Oloko et al, 2022). This also aligns with gendered resilience studies, which argue that a gendered view of resilience is critical to advancing an inclusive and sustainable understanding of resilience approaches (see, for example, Smyth and Sweetman, 2015).…”
Section: Conceptualising Resiliencementioning
confidence: 85%
See 1 more Smart Citation
“…Specifically, we focus on how women in the SSF sector have responded to the disruptions caused by COVID-19 and assess the resilience-potential of these responses based on how these responses interact with their pre-existing SSF vulnerabilities. This line of inquiry has critical importance, given the high degree of vulnerability that existing research within SSF has recognised among women within this sector (see, for instance, Thorpe et al, 2014;Harper et al, 2017;Galappaththi et al, 2022;Oloko et al, 2022). This also aligns with gendered resilience studies, which argue that a gendered view of resilience is critical to advancing an inclusive and sustainable understanding of resilience approaches (see, for example, Smyth and Sweetman, 2015).…”
Section: Conceptualising Resiliencementioning
confidence: 85%
“…These dynamics produce gendered vulnerabilities that further disadvantage them (see: Isaacs et al, 2022). Gendered definitions of fishing (Harper et al, 2017;Galappaththi et al, 2022), earnings gaps (Thorpe et al, 2014;Du Preez, 2018) and social expectations (Oloko et al, 2022) conspire to render women invisible in SSF, as their participation in SSF continues to be concentrated in the informal economy where they are excluded from institutional consideration or social protections (Okafor-Yarwood and van den Berg, 2021). Specifically, women's fisheries work is often perceived merely as an extension of their gendered everyday lives (Harper et al, 2017), limiting their livelihood security and making them particularly vulnerable to disruptions that threaten their already precarious livelihoods.…”
Section: Conceptualising Resiliencementioning
confidence: 99%
“…Capacity of women involved in SSF must be developed to fully enhance their roles in fishery resource management and to have a more active role in decision making at all levels. Inclusion of representative women's voices in fisheries governance can be crucial (Galappaththi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of representative women's voices in fisheries governance can be crucial (Galappaththi et al, 2022).…”
Section: Global Policy Implicationsmentioning
confidence: 99%
“…They found that the absorbable areas related to fisheries management, operations, and research needed more political, social, and relationship input. Similarly, Drakopulos (2022) and Galappaththi et al (2022) investigated women's experiences influencing and shaping small‐scale fisheries governance. They did this by referring to the institutional contexts within which women participate, reflecting a broad spectrum of arrangements, including interactions with rules and regulations; participatory arrangements like co‐management; and informal norms, customary practices, and relational spaces.…”
Section: Literature Reviewmentioning
confidence: 99%